Experience with undergraduate training in rheumatology in Poland and some new suggestions - Zimmermann-Górska, Irena (Reumatologia/Rheumatology, 2006)
We have in Poland 11 universities with medical faculties, where Polish and foreign students are taught rheumatology as a part of internal medicine. Students are taught in the 4th, 5th or 6th year of study and rheumatology is covered in 20-40 h of activities – mainly at the bedside and in outpatient clinics. In order to give them essential knowledge of rheumatology we have prepared short textbooks, in both Polish and English. The main aim of our teaching is to prepare students for the role of general practitioner. From my experience of teaching medical students I feel that one disadvantage of the ”Global core recommendations for a musculoskeletal undergraduate curriculum” is that it includes many symptoms which rightly belong to orthopaedics and surgery and not to rheumatology. Before going into practice the student should be able to diagnose and determine the therapeutic interventions required in ”true”, non-traumatic, rheumatic diseases. It is suggested therefore that a programme of an educational course in rheumatology for undergraduates, both ”on-line” and in the form of a short but focussed textbook of knowledge for European medical students, should be prepared.